GAMBARAN PERILAKU KONSUMSI ALKOHOL PADA MASYARAKAT DESA PAKISAN KABUPATEN BULELENG - Martayani, Nyoman Mita; Widyanthari, Desak Made; Antari, Gusti Ayu Ary; Sawitri, Ni Komang Ari (Coping: Community of Publishing in Nursing; Vol 12 No 4 (2024): Agustus 2024, 2025)
Alcohol is an addictive substance that has the potential to lead to addiction. Alcohol-containing drinks can cause harm and put the user and others in danger if they are regularly taken in excess of the recommended dosage and misused. The purpose of this study is to characterize the drinking habits of the people living in Pakisan Village.The design of this research is quantitative descriptive with a cross sectional approach. The sample consisted of 82 respondents in Pakisan Village who were selected using purposive sampling. The measuring tool used in this research is a questionnaire describing alcohol consumption behavior. The research was conducted from October to November 2023. According to the research data on participant characteristics, 98.8% of research respondents were male, 42.7% were between the ages of 26 and 35, 92.7 percent were employed, 65.9% were married, 59.8% had completed high school, and 59.8% made less money than the minimum wage (Rp. 2,542,312.33). According to studies on alcohol consumption patterns, most people drink up to 31.7% of alcoholic beverages like palm wine and arak, 35.4% of the time, and 37.8% of them consume three to five shots or more. The majority of these drinks are consumed for entertainment purposes, accounting for 63.4% of the total. Up to 58.5% of research participants drank more alcohol than is considered safe, which led to adverse consequences such nausea, vomiting, lightheadedness, and loss of self-control. Most research participants had never been taught or educated about alcohol, and most were unaware of the risks associated with alcohol intake. It is envisaged that health officials will use this research as a guide when developing public alcohol consumption reduction initiatives.